Effect of region-wide use of prehospital stroke triage scale on management of patients with acute stroke. (19th August 2021) - Araki, Hayato; Uchida, Kazutaka; Yoshimura, Shinichi; Kurisu, Kaoru; Shime, Nobuaki; Sakamoto, Shigeyuki; Aoki, Shiro; Ichinose, Nobuhiko; Kajihara, Yosuke; Tominaga, Atsushi; Naka, Hiromitsu; Mizoue, Tatsuya; et al.
Abstract : Background: Prehospital stroke triage scales help with the decision to transport patients with suspected stroke to suitable hospitals. Objective: To explore the effect of the region-wide use of the Japan Urgent Stroke Triage (JUST) score, which can predict several types of stroke: large vessel occlusion (LVO), intracranial hemorrhage (ICH), subarachnoid hemorrhage (SAH), and cerebral infarction other than LVO (CI). Methods: We implemented the JUST score and conducted a retrospective and prospective multicenter cohort study at 13 centers in Hiroshima from April 1, 2018, to March 31, 2020. We investigated the success rate of the first request to the hospital, on-scene time, and transport time to hospital. We evaluated the door-to-puncture time, puncture-to-reperfusion time, and 90-day outcome among patients with final diagnoses of LVO. Results: The cohort included 5141 patients (2735 before and 2406 after JUST score implementation). Before JUST score implementation, 1269 strokes (46.4%) occurred, including 140 LVO (5.1%), 394 ICH (14.4%), 120 SAH (4.4%), and 615 CI (22.5%). The JUST score was used in 1484 (61.7%) of the 2406 patients after implementation, which included 1267 (52.7%) cases of stroke (186 LVO (7.7%), 405 ICH (16.8%), 109 SAH (4.5%), and 567 CI (23.6%)). Success rate of the first request to the hospital significantly increased after JUST score implementation (76.3% vs 79.7%, p=0.004). JUST score implementation significantly shortened the door-to-puncture time (84 vs 73 min, p=0.03), but the prognosis remained unaltered among patients with acute LVO. Conclusions: Use of prehospital stroke triage scales improved prehospital management and preparation time of intervention among patients with acute stroke.